The Privilege of Induction Avoidance and Calcineurin Inhibitors Withdrawal in 2 Haplotype HLA Matched White Kidney Transplantation. Issue 3 (March 2017) - Brifkani, Zaid; Brennan, Daniel C.; Lentine, Krista L.; Horwedel, Timothy A.; Malone, Andrew F.; Delos Santos, Rowena; Maw, Thin Thin; Alhamad, Tarek
Abstract : Background: White recipients of 2-haplotype HLA-matched living kidney transplants are perceived to be of low immunologic risk. Little is known about the safety of induction avoidance and calcineurin inhibitor withdrawal in these patients. Methods: We reviewed our experience at a single center and compared it to Organ Procurement and Transplantation Network (OPTN) registry data and only included 2-haplotype HLA-matched white living kidney transplants recipients between 2000 and 2013. Results: There were 56 recipients in a single center (where no induction was given) and 2976 recipients in the OPTN. Among the OPTN recipients, 1285 received no induction, 903 basiliximab, 608 thymoglobulin, and 180 alemtuzumab. First-year acute rejection rates were similar after induction-free transplantation among the center and induced groups nationally. Compared with induction-free transplantation in the national data, there was no decrease in graft failure risk over 13 years with use of basiliximab (adjusted hazard ratio [aHR], 0.86; confidence interval [CI], 0.68-1.08), Thymoglobulin (aHR, 0.92; CI, 0.7-1.21) or alemtuzumab (aHR, 1.18; CI, 0.72-1.93). Among induction-free recipients at the center, calcineurin inhibitor withdrawal at 1 year (n = 27) did not significantly impact graft failure risk (HR, 1.62; CI, 0.38-6.89). Conclusions: This study may serve as a foundation for further studies to provide personalized, tailored, immunosuppression for this very low-risk population of kidney transplant patients.